Structure and function of learning flights in bees and wasps - Zeil, Jochen; Kelber, Almut; Voss, Rüdiger (Journal of Experimental Biology, 1996)
Bees and wasps perform systematic flight manoevres when they leave their nest or a foodplace, during which they acquire or update their visual memory of the goal location. In a typical learning flight, the insect backs away from the goal in a series of arcs that are roughly centred on the goal. The mean rate of turning is rather constant and tends to balance the angular speed at which the arc is described. As a result, the insect views the goal at relatively fixed retinal positions in its left and right visual field, depending on flight direction. The general direction in which the insect backs away from the goal and the transition from one arc segment to the next are influenced by the local scene and by compass cues. Insects returning to the goal repeat some of the flight manoeuvres of their preceding learning flights. Their orientation in space and the retinal positions at which they view nearby landmarks are similar. One important function of learning flights appears to be the acquisition of visual depth information. We review the consequences of the structure of learning flights for visual information processing and discuss how they may relate to the acquisition of a visual representation and the task of pinpointing the goal.